Adaptive Second Order Sliding Mode Control for the Regulation of Active Magnetic Bearing. (2020) - Saha, Sudipta; Amrr, Syed Muhammad; Nabi, M.
Abstract: The active magnetic bearing (AMB) has been widely used for the corrective actions in the fast rotating machines, which often faces the problem of deviation in the shaft position. The AMB system, with the use of an electromagnetic control force, regulates the displaced rotor and maintains it to the nominal location. This paper investigates the application of a sliding mode based robust control technique for the control design of five degrees of freedom (DOF) AMB system, which is subjected to the model uncertainties and bounded disturbances with unknown bounds. The proposed controller is formulated by combining the adaptive, integral second-order sliding mode control (ISOSMC) techniques. The adaptive laws estimate the gains of the controller without the upper bound information of the lumped disturbance. The use of ISOSMC ensures the robustness of the controller, along with the finite-time convergence of system states. Moreover, the ISOS also significantly reduces the chattering in the control input. The theoretical analysis under the proposed scheme for the AMB system guarantees the finite-time convergence using the Lyapunov and homogeneity theories. At last, numerical analysis is carried out to validate the offered methodology.